MODIFIED LAUTENBACH TECHNIQUE AND EXTERNAL FIXATION AS A TREATMENT FOR INFECTED NON-UNION OF THE SUBTROCHANTER FEMUR: A CASE REPORT - Mouli Edward; Teddy Heri Wardhana; Erfan Nasrullah (Journal Orthopaedi and Traumatology Surabaya)
Infected non-union is still a challenging orthopedic case to treat. Up until present day, there is no any established protocol to treat infected non-union of femur. Infection at subtrochanter femur specifically poses extra challenge as aforementioned location is affected by great tension and compression force. In this report, we present a 20-yo woman with infected subtrochanter femur following open reduction internal fixation (ORIF)with angle blade plate (ABP) 95o. One stage surgery was performed involving implant removal, debridement, definite external fixation, and antibiotic delivery using modified Lautenbach technique. Four years after trauma, the patient was capable of independent mobilization without aid. No infection recurrence was found, and Haris Hip Score was 91 (excellent). Based on the result of this case, definite external fixation and modified Lautenbach technique in one stage surgery can be a viable option in treating infected non-union of subtrochanter femur.